2008
DOI: 10.2522/ptj.20080031
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Diabetes: Opportunities for Prevention Through Policy

Abstract: Over the past decade, the prevalence of type 2 diabetes mellitus has reached epidemic levels in the United States and other developed countries. With a concomitant rise in obesity levels in the United States and advances in the treatment of diabetes and its complications, the prevalence of diabetes is expected to continue to rise through the year 2050. Despite strong evidence that regular physical activity can prevent or delay the onset of diabetes, too many Americans are not meeting the recommended levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 62 publications
0
10
0
3
Order By: Relevance
“…In addition, other sources have advocated expanding the role of physiotherapists beyond that of exercise prescription when caring for this population. 12,[17][18][19] von Lengerke and colleagues 17(p.538) posited that nonphysician health professionals ''may have even better opportunities than physicians to encourage the use of early detection and screening . .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other sources have advocated expanding the role of physiotherapists beyond that of exercise prescription when caring for this population. 12,[17][18][19] von Lengerke and colleagues 17(p.538) posited that nonphysician health professionals ''may have even better opportunities than physicians to encourage the use of early detection and screening . .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Physiotherapists need to capitalize on these opportunities, given that compared with adults of normal weight, adults who are obese are more likely to access PT services in outpatient settings, 17 as well as more likely to require in-patient rehabilitation after discharge from an acute care hospital after elective hip-replacement surgery. 20 Deshpande and colleagues 18 proposed that a conceptual shift toward primary and secondary prevention is required in PT practice, suggesting that physiotherapists engage further in school-based consultations, employee wellness and screening programmes, and communitybased activities to prevent sequelae of obesity. The CPA position statement on obesity also stated that physiotherapists are well suited to engage in health promotion, complication prevention, and management of conditions related to obesity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As it appears from the T2DM example shown, prevention requires the involvement of several professional disciplines, including medicine, behavioural science, nutrition, and physical activity. Clinical studies have consistently shown that diabetes can be prevented by lifestyle changes related to healthy nutrition, and an adequate amount of physical exercise and weight reduction (Deshpande, Dodson, Gorman, & Brownson, 2008). To build a strong prevention team and network of professionals, the aim is to engage experts from various backgrounds who have an interest in reducing the growing prevalence of T2DM and to strengthen the community action.…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) , dois (menos de 1%) apresentaram considerações sobre as alterações osteomusculares (22)(23) e três (menos de 1%) se referiram às alterações vasculares relacionadas ao DM (24)(25)(26) . Os demais 13 artigos abordaram a atuação preventiva do fisioterapeuta, sendo que apenas um (menos de 1%) destacou estratégias destinadas à prevenção da doença (27) e 12 (35%) referiram-se à prevenção secundária, envolvendo a educação em saúde e a prescrição de exercícios aeróbicos e terapêuticos (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) .…”
Section: Materiais E Métodosunclassified
“…Esta nova concepção é relevante para a prevenção do DM, sobretudo por meio da promoção da atividade física em escolas, ambiente de trabalho e nas comunidades. Ações de advocacy também são fundamentais, tendo o objetivo de estimular as pessoas a exigirem a implementação de políti-cas públicas e a criação de espaços que estimulem a prática de atividade física (27) . A atividade física entre pacientes com DM também é de suma importância, sendo o fisioterapeuta fundamental para a prescrição de exercícios (28) .…”
Section: (3) 14unclassified